Determination of Radiochemical Purity of 99mTc-DTPA Using One-System Method of Paper Chromatography - Maskur Maskur; Enny Lestari; Amal Rezka Putra; Dede Kurniasih; Endang Sarmini; Yayan Tahyan; Adang Hardi Gunawan; Arni Aries (The Journal of Pure and Applied Chemistry Research, 2019)
The more efficient and effective quality control techniques for 99mTc-DTPA are needed because 99mTc has a short half-life of around 6.0 hours. We have succeeded in developing a one-system of TLC for radiochemical purity testing system that is faster and more practical. Two-system method of TLC for radiochemical purity testing uses mobile phase of methyl ethyl ketone as an A and 0.9% sodium chloride solution as a B. One-system method uses the mobile phase of a mixture solution of acetone and 0.9% sodium chloride. In this study, the determination of radiochemical purity of the one-system of TLC has been successfully developed using the Whatman-1 paper stationary phase and the mixed mobile phase between acetone and 0.9% sodium chloride solution. The mobile phase of acetone: 0.9% sodium chloride with a ratio of 9:1 shows the most optimum results. This phase can separate 99mTc-DTPA (Rf = 0.4-0.6) from 99mTcO4- (Rf = 0.9-1.0) and 99mTcO2 (Rf = 0.0-0.1) as radiochemical impurities. This result shows that the one-system of TLC method can be used for radiochemical purity testing of 99mTc-DTPA radiopharmaceutical kits. This method can completely separate the product compound (99mTc-DTPA) from its impurities (99mTcO2 and 99mTcO4-).